2020
DOI: 10.1016/j.cgh.2019.11.036
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Acute Mountain Sickness by Unsedated Transnasal Esophagogastroduodenoscopy at High Altitude

Abstract: BACKGROUND AIMS It is not clear how rapid ascent to high altitude causes the gastrointestinal symptoms of acute mountain sickness (AMS). We assessed the incidence of endoscopic lesions in the upper gastrointestinal tract in healthy mountaineers after rapid ascent to high altitude, their association with symptoms, and their pathogenic mechanisms. METHODS In a prospective study, 25 mountaineers (10 female; mean age, 43.8y±9.5 y) underwent unsedated, transnasal esophago-gastroduodenoscopy in Zurich (490 m) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…The timing of anosmia and ageusia in our analysis is similar to previous reports, which found a mean of 3 days from illness onset to anosmia and ageusia in hospitalized and nonhospitalized COVID-19 patients (34,35). The later occurrence of gastrointestinal symptoms and rash among our participants could be related directly to the virus, linked to interventions (e.g., use of antimicrobial drugs or other medications), or, in the case of gastrointestinal symptoms, related to hypoxia (36)(37)(38)(39). We identified an overall progression of reported symptoms that is consistent with, although more detailed than, a recent metaanalysis of symptoms among persons with COVID-19 (20).…”
Section: Discussionsupporting
confidence: 88%
“…The timing of anosmia and ageusia in our analysis is similar to previous reports, which found a mean of 3 days from illness onset to anosmia and ageusia in hospitalized and nonhospitalized COVID-19 patients (34,35). The later occurrence of gastrointestinal symptoms and rash among our participants could be related directly to the virus, linked to interventions (e.g., use of antimicrobial drugs or other medications), or, in the case of gastrointestinal symptoms, related to hypoxia (36)(37)(38)(39). We identified an overall progression of reported symptoms that is consistent with, although more detailed than, a recent metaanalysis of symptoms among persons with COVID-19 (20).…”
Section: Discussionsupporting
confidence: 88%
“…This is important because systemic inflammation has a profound impact on hematopoiesis, gastrointestinal iron absorption, and ferritin plasma levels. 8,9 To assess whether increased ferritin serum levels, a marker for body iron stores, directly depend on a concomitant increase in Hb concentrations, we analyzed the interrelationship among altitude, Hb, ferritin, CRP, and BMI. Analysis of conscripts with normal Hb concentrations (,175 g/L), normal CRP (,5.0 mg/L), and normal BMI (18.5-24.9 kg/m 2 ) revealed that ferritin levels still increased significantly with altitude (Figure 2E).…”
mentioning
confidence: 99%
“…Other explanations for the above‐described findings can be postulated but seem unlikely: Impaired absorption of lipids can delay absorption of 13 C‐labeled fatty acids in intestinal disorders; however, the observations above require accelerated absorption of nutrition at HA and this is not consistent with reports in animals and humans, discussed above 17 . Moreover, there is no evidence of an increased postprandial blood flow of the mucosa or the intestine at altitude; mucosal blood flow is decreased in hypoxic conditions, which contributes to the high frequency of mucosal erosions documented in endoscopy at HA 17,24 . In the larger vessels like the hepatic portal vein, the postprandial blood flow is not altered by HA exposure 17 .…”
Section: Discussionmentioning
confidence: 98%